Study on land change based on principal component analysis. Issue 4 (March 2021) - Shen, Jing; Piao, Dongfan
Abstract: The Loess Plateau is the area with the most serious soil erosion and the most fragile ecological environment in China and even in the world. The deterioration of ecological environment may be closely related to unreasonable land use. In order to study the characteristics and driving factors of land use in small watershed of Loess Plateau, based on the land use data, DEM data and social data of Wuding River Basin in 1980, 1990, 2000, 2010 and 2018, this paper uses ArcGIS platform, land transfer matrix and land use dynamic degree to analyze them, and uses principal component analysis to discuss land use driving forces.